Binding partners regulate unfolding of myosin VI to activate the molecular motor. Issue 13 (15th July 2022) - dos Santos, Ália; Fili, Natalia; Hari-Gupta, Yukti; Gough, Rosemarie E.; Wang, Lin; Martin-Fernandez, Marisa; Aaron, Jesse; Wait, Eric; Chew, Teng-Leong; Toseland, Christopher P.
Abstract : Myosin VI is the only minus-end actin motor and it is coupled to various cellular processes ranging from endocytosis to transcription. This multi-potent nature is achieved through alternative isoform splicing and interactions with a network of binding partners. There is a complex interplay between isoforms and binding partners to regulate myosin VI. Here, we have compared the regulation of two myosin VI splice isoforms by two different binding partners. By combining biochemical and single-molecule approaches, we propose that myosin VI regulation follows a generic mechanism, independently of the spliced isoform and the binding partner involved. We describe how myosin VI adopts an autoinhibited backfolded state which is released by binding partners. This unfolding activates the motor, enhances actin binding and can subsequently trigger dimerization. We have further expanded our study by using single-molecule imaging to investigate the impact of binding partners upon myosin VI molecular organization and dynamics.